Not sure what you are asking. (a+1)(a+2) = a * a + a * 2 + 1 * a + 1 * 2 = a^2 + 3*a + 2, which is a polynomial of degree 2, hence a quadratic. To solve a quadratic equation that equal zero, it is necessary to find, in this case, the values of a that will make the quadratic equal to zero. In this case, it is easy to figure out since (a+1) = 0 only if a+1 = 0, which means that a = -1. Likewise, (a+2) = 0 only if a = -2. Notice that if a = -1 or a = -2 =0 then (a+1)*(a+2) = 0 since if one of the factors [that is, (a+1) or (a+2)) is equal to zero, then (a+1)(a+2) must also be zero